English Learners' Acquisition of Academic Vocabulary: Instruction Matters, but So Do Word Characteristics. Issue 3 (25th October 2020) - August, Diane; Uccelli, Paola; Artzi, Lauren; Barr, Christopher; Francis, David J.
Abstract: In this cluster randomized control trial study, the authors explored the efficacy of an intervention designed to improve second‐grade English learners' knowledge of challenging, high‐utility English vocabulary. The authors also examined whether the intervention had a differential effect on content words that differ on two attributes (cognate status and abstractness designation) and whether the effects lasted across time. Within schools, teachers were randomly assigned to treatment or control conditions, resulting in 12 treatment classrooms and 10 control classrooms. Teachers in the treatment condition developed vocabulary using six methods: interactive shared reading, direct instruction of individual words, instruction in cognate use, activities to foster word consciousness and reinforce instructed words, and use of visual and linguistic supports. Teachers in the control condition read the same books with the target vocabulary inserted into the stories. Findings on the curriculum‐based and standardized measure of vocabulary indicated that the intervention implemented for four 50‐minute lessons per week for 18 weeks was effective in helping English learners acquire challenging high‐utility school‐relevant vocabulary (Cohen's d = 1.88 for content words; d = 0.41 for connecting words; d = 0.47 for the Test of Oral Language Development). The effects differed by word characteristics, with higher effect sizes for words that are noncognates ( d = 1.57 for both concrete and abstract noncognates; d = 1.02 concrete cognates; d = 0.81 for abstract cognates). Ten months after the intervention, treatment students still outperformed control students on content vocabulary learned during the intervention ( d = 1.31). This study helps validate a multifaceted approach to vocabulary intervention and research.